DRUG UTILISATION, ADVERSE DRUG REACTION PROFILE AND TREATMENT OUTCOME OF PNEUMONIA IN UNDER-FIVE CHILDREN IN A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY. - Dash, Snehasini; Panda, Suvendu Kumar; Behera, Jayanti Prava; Mishra, Pratyush (Student’s Journal of Health Research Africa, 2025)
Backgrounds Childhood pneumonia is a leading cause of morbidity and mortality among children under 5 years old worldwide. Despite global efforts to prevent and manage this condition, the improper and irrational use of antimicrobials is one of the greatest hinderance to achieving the target. Objectives: The study aimed to evaluate the drug utilization pattern, treatment outcome, and monitoring of frequency and severity of Adverse Drug Reactions (ADRs) with its causality assessment among under-five pneumonia cases. Methods This observational cross-sectional study was conducted on 118 diagnosed cases of pneumonia aged 2 months to 5 years. Data were collected from treatment records and parents’ responses and analyzed using Microsoft Excel 2016 and SPSS version 22.0. Results Among 118 under-five pneumonia cases, 88.1% recovered and 11.9% required ICU care. Most were male (75.4%), aged 2–12 months (60.2%), and from rural areas (73%). Complications were linked to female gender and parental smoking. Adverse outcomes were associated with fever, cough, delayed treatment, prolonged hospitalization, and multiple antibiotic use. Prescription analysis (536 cases) showed polypharmacy (mean 4.52 drugs), universal antibiotic, and injection use, with 85.92% prescribed by generic name and 88.93% from the essential drug list. Of 50 ADRs, diarrhea (58%) from ceftriaxone was most common. Interpretation: Female gender and parental smoking were associated with higher ICU admissions, highlighting the need for targeted clinical strategies in managing pediatric pneumonia. Conclusion The study concluded that prompt and appropriate treatment is pivotal for resolving pneumonia in children and reducing morbidity and mortality. Monitoring prescriptions and drug utilization studies helps in detecting and reducing irrational prescribing while offering feedback to prescribers. Recommendation Raising awareness among healthcare providers and caregivers, regularly educating on proper antibiotic use, implementing prescribing guidelines, and involving patients in ADR reporting can enhance treatment outcomes and minimize adverse drug reactions in under-five pneumonia cases.